The Effectiveness Of Natural Coagulant Made From Averhoa bilimbi L. Juice, CaO and Alum To Improve The Quality Of River Water - Nasution, Emelia; Hasbi, M.; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Sail river is one of polluted rivers in Pekanbaru, it has low pH and DO and high TDS, TSS, turbidity and colors. The quality of the water can be improved by flocculation – coagulation process. To understand the effectiveness of Averrhoa bilimbi L. juice as natural coagulant, a study has been conducted in January – April 2016. There were 4 treatments applied, P0 (control, no A. bilimbi juice), P1 (25 ml/L), P2 (35 ml/L) and P3 (45 ml/L). The juice was added to 10 L of river water, were stirred for 2 minutes and were sample for water quality study within 2 hours. Parameters measured were TSS, turbidity and colour. The treated water was then used for rearing C. carpio. By the for 4th day the survival rate of the fish was noted. The best treatment was obtained in P2, as the TSS decrease from 1,725 mg/L to 37 mg/L, the turbidity decrease from 906.67 NTU to 26.41 NTU, the color reduced from 1.79 TCU to 0.08 TCU and the survival rate of the fish was 83%. Based on data obtained, it was concluded that the juice of A. bilimbi can be used as a natural coagulants to improve the quality of river water.Keywords : Averrhoa bilimbi, river water, natural coagulant, Cyprinus carpio